The Enhancing the Impact of the BIDARI Program in Kuantan Singingi Through Mentoring and Capital Support - Teddy Niswansyah; Alsar Andri; Fauzil Hasdi; Gio Vani Jefri; Zaky Al Fadli; Al Fikri Fauzi (International Journal of Community Service Implementation, 2026)
This study aims to analyze the effectiveness of the BIDARI program in strengthening the economic independence of micro, small, and medium enterprises operated by zakat beneficiaries in Riau Province. The program applies an integrated empowerment model combining productive capital assistance, structured mentoring, business legalization support, rebranding, and marketing facilitation. This research employs a community-based approach with descriptive qualitative analysis based on program implementation, mentoring activities, and beneficiary development outcomes. The results indicate that capital assistance becomes more effective when accompanied by continuous supervision and capacity building. Participants show improvements in business management practices, financial organization, product quality, legal compliance, and market access. Support in obtaining business permits and halal certification enhances product credibility, while packaging improvement and digital marketing initiatives increase competitiveness in local markets. Although challenges such as limited digital literacy and uneven business readiness remain, adaptive mentoring strategies help address these constraints. In conclusion, the BIDARI program demonstrates that integrated productive zakat empowerment can promote sustainable business growth and contribute to poverty reduction by transforming beneficiaries into more independent and competitive entrepreneurs.